Efektivitas Penggunaan E-Learning Mahasiswa Fakultas Ilmu Sosial UIN Sumatera Utara di Masa Pandemic Covid-19 - Franindya Purwaningtyas; Alfany Umar; Inggrid Masita Dewi; Salsabila Melfan; Ummi Afzah Amirah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
During the Covid-19 pandemic, many things happened that affected every field of movement, especially in the health sector. This also has a major impact on the education sector. So, under these circumstances, agencies and institutions are taking action to reduce the risk of Covid-19. Because of this, the government decided to carry out the educational process by utilizing e-learning media. E-learning may be better known by the general public with the online (in-network) learning process. This study aims to determine the effectiveness of FIS students at UIN North Sumatra in using e-learning during the Covid-19 pandemic. The population used was FIS students at UIN North Sumatra and the sample consisted of 94 students. Research using quantitative with descriptive analysis methods and Level of Achievement of Respondents. The results showed that the indicators of recipient or user were 84.96% in the good category, Message Content 90.43% in the good category, Communication Media 81.17% in the good category, Message Format 76.03% in the good enough category, Message Source 74.79% in the enough category good, Timeliness 82.34% is in good category. And from all indicators, the percentage for the effectiveness of using e-learning for FIS UIN North Sumatra students during the Covid-19 pandemic was 81.61% and was in the good category. Keywords: Effectiveness, E-Learning, Covid-19